Here's the question you clicked on:
Coolme34
3 ( m - 6 ) + 2 ( m + 5 ) = 2; m =
\[ 3 ( m - 6 ) + 2 ( m + 5 ) = 2 \rightarrow 3m - 18 + 2m + 10 = 2 \rightarrow 5m - 8 = 2 \rightarrow 5m = 10 \rightarrow m = \boxed {2}. \]
|dw:1349123069420:dw|
@laraalexis82298 I can't see your entire image. If you wanted to say something to me, could you please post it?
All that is missing is the "you" part. It cut off the "u" in "you". That's all. :) But, if you want, I can post it. "Are you sure that you wrote the problem down correctly? I am getting an improper fraction... @Ahaanomegas, can you draw that out for me, so that I can see that clearer? Thanks :)". That's what I wrote...